Optimalisasi Supply Chain Management Guna Mengatasi Tantangan Persediaan Pada Industri Tape Di Raja Tape Bondowoso - Puspita Arya Pangastuti; Hery Murnawan (Jurnal Serambi Engineering, 2024)
The level of competition in the tape industry is often discussed nowadays, because of the promising business opportunities for tape as a souvenir product typical of the city of Bondowoso. Apart from that, the decline in the availability of cassava raw materials since the Covid-19 pandemic has encouraged tape producers to look for raw materials of the best quality, which has resulted in a mismatch between the acquisition of raw materials and the level of demand. Raja tape is one of the MSMEs operating in the food sector located in Bondowoso, East Java. Raja Tape often experiences shortages of cassava raw materials. Often yellow cassava supplies are taken to middlemen even though the price difference is different, which results in an imbalance between demand and supply in the following period. After conducting observations andinterviews with the owner of Raja Tape, the researchers identified supply chain management problems, the first of which was due to the lack of yellow cassava raw materials. Apart from that, the supply chain flow of tape products, starting from raw materials, land area requirements and seeds from raw material components needed to fulfill production. The results of this research obtained the needs of each component in the tape supply chain, namely land area and cassava, banana and bamboo tree seeds. This was done todetermine optimal needs for tape supplies at Raja Tape.